Evaluation of Manganese Oxide Octahedral Molecular Sieves for CO and C3H6 Oxidation at Diesel Exhaust Conditions - Wang, Xin; Tan, Wei; Guo, Kai; Ji, Jiawei; Gao, Fei; Tong, Qing; Dong, Lin (Frontiers in Environmental Chemistry, 2021)
Mn-based materials have been widely applied in the environmental catalysis field for their excellent redox properties. Here, three kinds of crystallite manganese oxides (pyrolusite, cryptomelane and todorokite) with different tunnel sizes (MnO(1×1), MnO(2×2) and MnO(3×3)) were prepared by hydrothermal method, and their catalytic performance in complete oxidation of diesel vehicle exhaust were tested. The highest catalytic oxidation activity was achieved on MnO(3×3) when compared with that on MnO(1×1) and MnO(2×2). Via a series of characterizations, such as X-ray powder diffraction, N2-sorption experiments, temperature-programmed reduction by H2, transmission electron microscope, scanning electron microscope, and X-ray photoelectron spectroscopy, etc., it was found that the catalytic activity was mainly determined by the tunnel structure, specific surface area, and redox ability.